CDO and HAC - Barbara Choroś; Wolfgang Karl Härdle; Ostap Okhrin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Modelling portfolio credit risk is one of the crucial challenges faced by financial services industry in the last few years. We propose the valuation model of collateralized debt obligations (CDO) based on copula functions with up to three parameters, with default intensities estimated from market data and with a random loss given default that is correlated with default times. The methods presented are used to reproduce the spreads of the iTraxx Europe tranches. We apply hierarchical Archimedean copulae (HAC) whose construction allows for the fact that the risky assets of the CDO pool are chosen from six different industry sectors. The dependence among the assets from the same group is specified with the higher value of the copula parameter, otherwise the lower value of the parameter is ascribed. The copula with two and three parameters models the relation between the loss given default and the default times. Our approach describes the market prices better than the standard pricing procedure based on the Gaussian distribution.
Keywords: C13; G12; G13; G21; 330; CDO; CDS; multivariate distributions; Copulae; correlation smile; loss given default; Finanzderivat; Kreditrisiko; Wertpapieranalyse; Volatilität; Kopula (Mathematik); Verlust; Theorie; Europa